Customer Satisfaction Analysis on the Integration of Bus Transit System in Semarang - Ma`ruf Tsaghani Purnomo; Hera Widyastuti (Institut Teknologi Sepuluh Nopember, 2023)
Trans Semarang and Trans Jateng are the service providers of Semarang bus transit system. Both services still operate independently and are not fully integrated. In addition, previous research has shown that multi-services integration in Semarang bus transit system is a necessity and considered important by customers. Therefore, an improvement of multi-services integration in Semarang bus transit system based on customer satisfaction is needed. The survey method used is questionnaire containing integration attributes that describe the satisfaction and expectations of customers. This research uses Importance-Performance Analysis, Kano model, and Quality Function Deployment method to obtain improvement priorities based on 150 respondents which have traveled with Trans Semarang and Trans Jateng in one trip. The result of this research indicates that 10 improvement that can be implemented in Semarang bus transit system multi-services integration which are prioritized from integration of multi-services information technology, provision of single ticket, and re-adjustment of time tables.